Oral communication and auditory skills of hearing impaired children and adolescents and the speech therapy rehabilitation process - Bicas, Rafaela Da Silva; Guijo, Laura Mochiatti; Delgado-pinheiro, Eliane Maria Carrit (ABRAMO Associação Brasileira de Motricidade Orofacial, 2017)
ABSTRACTPurpose: to analyze auditory and oral communication behaviors in a group of children and adolescents, users of cochlear implants and to establish a relationship with factors that interfere with aural rehabilitation.Methods: participants were 13 children or adolescents with profound bilateral sensorineural hearing loss. Standardized procedures were applied to check: the auditory and oral communication behaviors of participants and their relationships with the child's age at diagnosis period; the interval between diagnosis and intervention, adaptation onset of the cochlear implant; the hearing age and aural rehabilitation period.Results: statistically significant data were found to correlate the interval between diagnosis and intervention with the scores in the evaluation procedures of oral communication.Conclusion: there was a significant impact on the development of oral communication when the period elapsed between the diagnosis and intervention was analyzed, in such way that the faster the intervention time, the better the results. It was also evident that the earlier the beginning of the use of cochlear implants, the greater the hearing age, and the longer the rehabilitation period, the better the scores in the procedures that evaluated auditory and verbal development.

RESUMOObjetivo: analisar os comportamentos auditivos e de comunicação oral em um grupo de crianças e adolescentes usuários de implante coclear e estabelecer relações com fatores que interferem na reabilitação auditiva.Métodos: participaram deste estudo 13 crianças ou adolescentes com deficiência auditiva sensorioneural profunda bilateral. Foram aplicados procedimentos padronizados para verificar: o comportamento auditivo e de comunicação oral dos participantes e estabelecidas relações com a idade da criança no período do diagnóstico; o intervalo entre o diagnóstico e a intervenção, época de ativação do implante coclear; a idade auditiva e o período de reabilitação auditiva.Resultados: foram encontrados dados estatisticamente significantes ao correlacionar o intervalo entre o diagnóstico e a intervenção com os escores dos procedimentos de avaliação da comunicação oral.Conclusão: houve impacto significante no desenvolvimento da comunicação oral quando analisado o período transcorrido entre o diagnóstico e a intervenção, de tal forma que quanto mais rápida a intervenção, melhores os resultados. Foi evidente também que quanto mais precoce o início da utilização do implante coclear, maior idade auditiva e maior o período de reabilitação, melhores foram os escores nos procedimentos que avaliaram desenvolvimento auditivo e verbal.
Habilidades auditivas e de comunicação oral de crianças e adolescentes deficientes auditivos e o processo de reabilitação fonoaudiológica
Keywords: Hearing Loss; Cochlear Implant; Language; Auditory Perception; Perda Auditiva; Implante Coclear; Linguagem; Percepção Auditiva